Peningkatan Kemampuan Menulis Fabel Menggunakan Model Pembelajaran Example Non Example pada Siswa Kelas VII SMP Negeri Muara Beliti - Toriyani, Seprida; Sarwono, Sarwit; Gumono, Gumono (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this study was to describe the improvement of the process and the results of the ability to write fables using the example non example learning model for grade VII.3 students of SMP Negeri Muara Beliti for the 2018/2019 academic year. This research is a classroom action research consisting of two cycles, namely cycle I and cycle II. The data collection methods used were the observation method and the fable writing assignment test method. Data analysis techniques are data reduction, descriptive presentation (narrative, visual images, tables) with a systematic and logical flow of presentation, and the conclusion of the results presented based on indicators of research success. The results showed that the example non example learning model could improve the quality of the process and the results of learning to write fables for seventh grade students of SMP Negeri Muara Beliti in the 2018/2019 academic year. This is evidenced by the increase in teacher activity in cycle I reaching 65.3%, increasing to 94.4% in cycle II. In the first cycle, student learning activities, namely 71.9%, increased to 81.3% in the second cycle.